Hard work, long hours, and Singaporean young adults' health—A qualitative study - Leu, Jodie; Rebello, Salome A.; Sargent, Ginny M.; Kelly, Matthew; Banwell, Cathy (Frontiers in Public Health, 2023)
Background: As young adults in their twenties to thirties transition towards new careers and independence, their dietary and physical activity practices often change, increasing their risk of weight gain. This study explored the ways that Singaporean young adults perceived and experienced the interaction between their working hours, work, and health practices. Methods: This research used semi-structured interviews to explore the perspectives and experiences of participants. Purposive and snowball sampling was used to recruit 15 men and 18 women, aged 23 to 36, who had worked full time at their respective jobs in Singapore for at least one year. An inductive and deductive thematic analysis approach was employed. Results: Young working adults’ commitment to work was driven by a hard-working culture, a desire to attain better jobs and remuneration, and to fulfil cultural expectations to support their multi-generation families. Their non-work time was largely spent recuperating from work by socializing over food and in sedentary activities. Conclusions: For young working adults, long work hours are normalised, even though they are a barrier to healthy diets and physical activity. Existing social and institutional norms support a culture that values commitment to work and encourages young adults to devote long hours to building a sound financial future and achieving personal and cultural aspirations. These findings have implications for long-term population health and should be considered in health promotion activities targeting young adults and barriers.